Oral glucose tolerance test unravels circulating miRNAs associated with insulin resistance in obese preschoolers. Issue 3 (5th April 2016) - Masotti, A.; Baldassarre, A.; Fabrizi, M.; Olivero, G.; Loreti, M. C.; Giammaria, P.; Veronelli, P.; Graziani, M. P.; Manco, M.
Summary: Background: Circulating microRNAs (miRNAs) may act as biomarkers of metabolic disturbances. Objective: The aim of this study was to identify serum miRNAs signature of early insulin resistance in obese preschoolers. Methods: Twelve obese children, aged 2–6 years, six insulin resistant (IR) and six controls were selected being age‐matched, sex‐matched and body mass index‐matched. Profiling of 179 circulating miRNAs, known to be widely expressed in the bloodstream, was investigated by quantitative polymerase chain reaction at fasting and 120 min following a standard oral glucose tolerance test (OGTT). Results: Twenty‐one miRNAs were differentially regulated in IR obese preschoolers. miR‐200c‐3p, miR‐190a and miR‐95 were differently regulated both at fasting and 120 min after the OGTT. In controls, the fold changes of some miRNAs were correlated with Δglucose0‐120 (miR‐660, miR‐26b‐5p and miR‐22‐3p: p = 0.005 for all) and Δinsulin0‐120 (miR‐660 and miR‐22‐3p: p = 0.02 for both and miR‐423‐5p: p = 0.042). In IR patients, miR‐1 fold changes were correlated with Δglucose0‐120 ( r = −0.786; p = 0.036) and Δinsulin0‐120 ( r = −0.821; p = 0.023). Conclusions: Our study identifies circulating miR‐200c‐3p, miR‐190a and miR‐95 as biomarkers of insulin resistance in obese preschoolers, being differentially regulated in IR patients both in fasting condition and after the OGTT. Expression of some circulating miRNAs seems reflecting glucose and insulin excursion following the OGTT differently in controls and IR obese preschoolers.